2012
DOI: 10.1002/mbo3.26
|View full text |Cite
|
Sign up to set email alerts
|

Tellurite enters Escherichia coli mainly through the PitA phosphate transporter

Abstract: Several transporters suspected to be involved in tellurite uptake in Escherichia coli were analyzed. Results showed that the PitA phosphate transporter was related to tellurite uptake. Escherichia coli ΔpitA was approximately four-fold more tolerant to tellurite, and cell viability remained almost unchanged during prolonged exposure to the toxicant as compared with wild type or ΔpitB cells. Notably, reduced thiols (toxicant targets) as well as superoxide dismutase, catalase, and fumarase C activities did not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 40 publications
3
34
1
Order By: Relevance
“…These findings were subsequently confirmed[21] and it was concluded that tellurite is transported into cells of E. coli via a phosphate transport system, EcPitA. Recently, a more detailed analysis of tellurite transport in E. coli concluded that the EcPitA system has indeed a relevant role at longer exposures to With a role of acetate permeases involved in the bacterial transport of tellurite now established, in the present work we have functionally and structurally identified two types of ActPs, RcActP1 and RcActP2, assigning to the latter the bulk of transport of tellurite inside the cells.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…These findings were subsequently confirmed[21] and it was concluded that tellurite is transported into cells of E. coli via a phosphate transport system, EcPitA. Recently, a more detailed analysis of tellurite transport in E. coli concluded that the EcPitA system has indeed a relevant role at longer exposures to With a role of acetate permeases involved in the bacterial transport of tellurite now established, in the present work we have functionally and structurally identified two types of ActPs, RcActP1 and RcActP2, assigning to the latter the bulk of transport of tellurite inside the cells.…”
supporting
confidence: 72%
“…The uptake of tellurite by the two carriers PitA and ActP2 is inhibited by the physiological substrates phosphate and acetate, respectively [18,21]. By using the two competitor substrates, it should be possible to determine the contribution of the two carriers when are simultaneously present in E. coli.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 3 more Smart Citations